A plasmid module for PCR-based gene modification for the accurate measurement of vacuolar delivery of specific proteins in yeast Saccharomyces cerevisiae - Jakob Valdbjørn Kanne; Fulvio Reggiori (Autophagy Reports)
Monitoring the delivery of single proteins and protein complexes to the vacuole by autophagy or other processes in yeast Saccharomyces cerevisiae mainly relies on western blot or fluorescence microscopy analyses using endogenous tagging of the protein of interest with GFP. However, these approaches are semi-quantitative and next to impossible with proteins of low abundancy because of the insensitive nature of the methods. Here, we describe the creation of a new PCR-based integration cassette to endogenously tag specific proteins with the truncated version of the vacuolar phosphatase Pho8. The vacuolar activation of Pho8 allows the quantitative measurement of vacuolar delivery using a colorimetric enzymatic assay. This approach has the advantages of a more quantitative interpretation of data and relies on the appearance of a signal rather than its disappearance. As a proof-of-principle, we examined the vacuolar delivery of known cargoes of bulk autophagy and endocytosis. This new system will be of great value to the whole community working within the field of autophagy and other transport pathways to the vacuole.